Fatigue in HIV/AIDS patients with comorbidities. - Corless, Inge B; Voss, Joachim G; Nicholas, Patrice K; Bunch, Eli H; Bain, Catherine A; Coleman, Christopher; Dole, Pamela J; Eller, Lucille S; Hamilton, Mary Jane; Holzemer, William L; Kemppainen, Jeanne K; Kirksey, Kenn M; et al. (Applied nursing research : ANR, 2008)
Fatigue has been identified as a key complaint among patients with HIV/AIDS. Although having more than one disease is expected to increase symptom severity, this relationship has not been explored extensively. We investigated differences in fatigue severity together with the impact of demographic factors and the number of comorbidities and symptoms among patients with and those without comorbidities at 18 international clinical and community sites. Specific comorbidities and the number of symptoms associated with increased fatigue severity. Only by distinguishing fatigue as to its causes and patterns will health care providers be able to intervene specifically and thus more effectively.
Keywords: Adult; Aged; Aged, 80 and over; Case-Control Studies; Comorbidity; Fatigue; Female; HIV Infections; Humans; Male; Middle Aged; Models, Theoretical; Nursing Assessment; Prevalence; Regression Analysis; Risk Factors; United States